2011
DOI: 10.24908/pceea.v0i0.3717
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Design of a Multi-Layered Dust Protection System for Optical Instruments Operating in the Lunar Environment

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Bivalve class. Further investigation by Davidson et al (2009) revealed that the bivalve class of mollusks, including scallops, clams, oysters, and mussels, have evolved for life in particulate-laden environments on earth, and protect themselves from both predation and environmental hazards, such as excessive particle intrusion, with their shells. The geometry of bivalve shells facilitates easy travel through sand and mud, while offering protection from hazards.…”
Section: Selected Analogiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Bivalve class. Further investigation by Davidson et al (2009) revealed that the bivalve class of mollusks, including scallops, clams, oysters, and mussels, have evolved for life in particulate-laden environments on earth, and protect themselves from both predation and environmental hazards, such as excessive particle intrusion, with their shells. The geometry of bivalve shells facilitates easy travel through sand and mud, while offering protection from hazards.…”
Section: Selected Analogiesmentioning
confidence: 99%
“…Human eye. Davidson et al (2009) report that an obviously analogous biological phenomenon for the protection of a visual sensing system from dust is that of the human eye. Different types of tears hydrate the eye and provide a barrier between dust and the sensitive tissues of the eye.…”
Section: Selected Analogiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group applied the natural language approach to a number of case studies, including design for remanufacture (Shu and Flowers 1999;Hacco and Shu 2002), authorized disassembly (Saitou et al 2007), microassembly (Shu et al 2003(Shu et al , 2006, sensing (Lenau et al 2008), redesign of fuel cells (Currie et al 2009;Ke et al 2009Ke et al , 2010, protection during hobbies , and protection from lunar regolith (Davidson et al 2009). Below, three of these case studies, incorporating insights as they were gained over the course of a decade, are presented.…”
Section: Examples Applying the Natural Language Approachmentioning
confidence: 99%
“…Therefore, strategies such as abscission and fainting are used before more critical damage to Fig. 3.8 CAD model of the bivalve-inspired lid assembly, adapted from Davidson et al (2009) the organism occurs. There is likely an abundance of preventive strategies in biology that are highly relevant to engineering, particularly the development of more sustainable products and processes.…”
Section: Identify Other Preventive Solutions In Biologymentioning
confidence: 99%